REVEALING THE MEANING OF NON-LITERAL LANGUAGES IN THAI COMMERCIALS USING THE LENS OF SEMIOLOGY - Santa Maya Pramusita (STKIP PGRI Jombang, 2020)
As a primary medium of marketing publication, a commercial can be easily found among society. Often, it is not only utilized to present new products or services, but also to convince people on a particular set of beliefs. To obtain this purpose, advertisers normally involve non-literal language which is known for its potentiality to grab audiences’ attention and to establish attractive promotion. In this study, the research uses semiology perspective to interpret the meaning of non-literal languages found in Thai commercials. It is done to provide readers with a vivid depiction on how Thai commercials convey their ideologies. As for the reason why the researcher chooses Thai commercials is because it contains appealing story plots and many non-literal languages. The analysis result implies that those Thai commercials use various non-literal languages such as hyperbole, simile, personification, metaphor, symbol, irony, and anaphora to introduce their products and to convey messages to audiences. In addition, non-literal languages within the Thai commercials also play a significant role in building a sense of humor and catch people’s attention to purchase their products.